ENVIRONMENTAL EDUCATION AND THE PROPER DISPOSAL OF MEDICATIONS IN HOME USE: A PEDAGOGICAL PROPOSAL IN THE CONTEXT OF SUSTAINABILITY APPLIED TO PRIMARY HEALTH CARE - Raphaela Leal Telles Menna Barreto; Glaucio Diré Feliciano (Artefactum - revista de estudos interdisciplinares, 2026)
The improper disposal of medicines in households is an increasing public health and environmental issue, posing risks of soil and water contamination as well as accidental intoxications. In this context, Primary Health Care (PHC) and nursing professionals play a key role in promoting environmental education regarding safe disposal practices. This article aims to review the scientific literature on the importance of environmental education in household medicine disposal, proposing a sustainable pedagogical approach applied to PHC. Through a narrative review in databases such as SciELO, LILACS, and Google Scholar, studies highlighting nursing leadership in community awareness were identified, emphasizing the educational role of these professionals in health promotion and sustainability. Findings indicate that integrated educational actions, based on participatory methodologies, can significantly reduce improper disposal and strengthen environmental awareness among the population.